Lattice BGK Model for Incompressible Axisymmetric Flows (Communications in Computational Physics, 2012)
In this paper, a lattice Boltzmann BGK (LBGK) model is proposed for simulating incompressible axisymmetric flows. Unlike other existing axisymmetric latticeBoltzmann models, the present LBGK model can eliminate the compressible effectsonly with the small Mach number limit. Furthermore, the source terms of the model aresimple and contain no velocity gradients. Through the Chapman-Enskog expansion,the macroscopic equations for incompressible axisymmetric flows can be exactly recovered from the present LBGK model. Numerical simulations of the Hagen-Poiseuilleflow, the pulsatile Womersley flow, the flow over a sphere, and the swirling flow in aclosed cylindrical cavity are performed. The results agree well with the analytic solutions and the existing numerical or experimental data reported in some previousstudies.